Discovery of genes related to formothion resistance in oriental fruit fly (Bactrocera dorsalis) by a constrained functional genomics analysis. Issue 3 (20th February 2015) - Kuo, T.C.‐Y.; Hu, C.‐C.; Chien, T.‐Y.; Chen, M.J.M.; Feng, H.‐T.; Chen, L.‐F. O.; Chen, C.‐Y.; Hsu, J.‐C.
Abstract Artificial selection can provide insights into how insecticide resistance mechanisms evolve in populations. The underlying basis of such phenomena can involve complex interactions of multiple genes, and the resolution of this complexity first necessitates confirmation that specific genes are involved in resistance mechanisms. Here, we used a novel approach invoking a constrained RNA sequencing analysis to refine the discovery of specific genes involved in insecticide resistance. Specifically, for gene discovery, an additional constraint was added to the traditional comparisons of susceptible vs. resistant flies by the incorporation of a line in which insecticide susceptibility was 'recovered' within a resistant line by the removal of insecticide stress. In our analysis, the criterion for the classification of any gene as related to insecticide resistance was based on evidence for differential expression in the resistant line as compared with both the susceptible and recovered lines. The incorporation of this additional constraint reduced the number of differentially expressed genes putatively involved in resistance to 464, compared with more than 1000 that had been identified previously using this same species. In addition, our analysis identified several key genes involved in metabolic detoxification processes that showed up‐regulated expression. Furthermore, the involvement of acetylcholinesterase, a known target for modification in insecticide resistance, was associated with three key nonsynonymous amino acid substitutions within our data. In conclusion, the incorporation of an additional constraint using a 'recovered' line for gene discovery provides a higher degree of confidence in genes identified to be involved in insecticide resistance phenomena.